2013
DOI: 10.1124/mol.112.084293
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacin I Inhibits Rac1 Activation in Breast Cancer Cells by a Reactive Oxygen Species-Mediated Mechanism and Independently of Janus Tyrosine Kinase 2 and P-Rex1

Abstract: The small GTPase Rac1 has been widely implicated in mammary tumorigenesis and metastasis. Previous studies established that stimulation of ErbB receptors in breast cancer cells activates Rac1 and enhances motility via the Rac-guanine nucleotide exchange factor P-Rex1. As the Janus tyrosine kinase 2 (Jak2)/ signal transducer and activator of transcription 3 (Stat3) pathway has been shown to be functionally associated with ErbB receptors, we asked if this pathway could mediate P-Rex1/Rac1 activation in response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 59 publications
2
27
0
Order By: Relevance
“…HRG and other ErbB ligands translocate P-Rex1 to the plasma membrane in a PI3K-dependent manner, leading to its activation. The requirement for P-Rex1 in HRG-induced Rac1 activation, ruffle formation, and motility, as well as its role in mammary tumorigenesis, has been unambiguously established by means of RNA interference (RNAi)-mediated loss of function approaches (36,40,43,44). Consistent with the established requirement for G␤␥ subunits in P-Rex1 activation, the GEF is also an effector of GPCRs (45).…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…HRG and other ErbB ligands translocate P-Rex1 to the plasma membrane in a PI3K-dependent manner, leading to its activation. The requirement for P-Rex1 in HRG-induced Rac1 activation, ruffle formation, and motility, as well as its role in mammary tumorigenesis, has been unambiguously established by means of RNA interference (RNAi)-mediated loss of function approaches (36,40,43,44). Consistent with the established requirement for G␤␥ subunits in P-Rex1 activation, the GEF is also an effector of GPCRs (45).…”
mentioning
confidence: 54%
“…Previously, we reported that treatment of breast cancer cells with HRG triggers a motile response that is mediated by the activation of Rac1 (35,36), a GTPase widely implicated in actin cytoskeleton reorganization, migration, and metastatic dissemination (37). Like most members of the Rho/Rac small G protein family, Rac1 is a molecular switch that cycles between inactive (GDP-bound) and active (GTP-bound) states.…”
mentioning
confidence: 99%
“…The effects of cucurbitacin I on Rac1 and RhoA were dependent on intracellular ROS generation as treatment with the ROS scavenger NAC ablated the response due to cucurbitacin I exposure. 136 Yu et al characterized the time course of RhoA activity following H 2 O 2 stimulation in MDCK (Madin-Darby canine kidney) cells. They found a ~1.75-fold increase in RhoA-GTP levels that peaked approximately 5 min post stimulation.…”
Section: Redox Regulation Of Rhoamentioning
confidence: 99%
“…In other words, 1 mg of CBI is equivalent to 112 mg of Bio 30 for therapy of cancers and many other PAK1-dependent diseases/disorders. This rough estimation is not far from the actual in vivo data where the daily dose of cucurbitacin B (1 mg/kg), closely related to CBI, and that of Bio 30 (50 mg/kg) are their effective dose to suppress the PAK1-dependent growth of pancreatic cancers or NF tumors in mice (14,20), suggesting that their in vivo bioavailability is quite similar.…”
Section: Anti-melanogenic Effect Of Cbi and Bio 30mentioning
confidence: 93%
“…In this study, we have chosen CBI and Bio 30 as potential model PAK1-blockers for the following reasons: CBI inhibits directly two activators (JAK2 and RAC) of PAK1 (19,20), while Bio 30 contains CAPE which down-regulates RAC by inhibiting directly AKR (AldoKeto-Reductase) 1B10 (21), and suppresses completely the PAK1-dependent growth of NF2-deficient tumor (schwannoma) in vivo (14).…”
Section: "Macaroni-western" Kinase Assay For the Inactivation Of Pak1mentioning
confidence: 99%